Target-sequence capture and high throughput sequencing identify a de novo CARD14 mutation in an infant with erythrodermic pityriasis rubra pilaris - Has, Cristina; Haußer-Siller, Ingrid (Acta dermato-venereologica, 2016)
Abstract is missing (Short communication)...
Gesehen am 30.04.2020